2004
DOI: 10.1007/s10350-003-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

A High Degree of Aneuploidy, Loss of p53 Gene, and Low Soluble p53 Protein Serum Levels Are Detected in Ulcerative Colitis Patients

Abstract: We demonstrate that in the colonic mucosa of ulcerative colitis patients, high levels of genomic instability, changes in p53 gene copy number, and lower levels of p53 in the serum directly correlate with the extent of disease duration and increased risk factors for colorectal cancer. Any of the measurements described herein can provide an acceptable prognostic tool in the assessment of colorectal cancer risk in ulcerative colitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Furthermore, percentage of patients with aneuploidy increases after duration of more than 10 years compared to patients with dysplasia findings that are found more often with disease duration of over 20 years [35]. Other studies confirmed that DNA aneuploidy is stable, widely spread (hence sampling error is minimal), may precede dysplasia (hence represents an early marker), and is evident 10 years after onset of colitis in young patients [23,25,55,63,68,75,76]. In addition to duration, aneuploidy correlates with extent of disease and is associated with total colitis [23,74].…”
Section: Surveillancementioning
confidence: 91%
See 4 more Smart Citations
“…Furthermore, percentage of patients with aneuploidy increases after duration of more than 10 years compared to patients with dysplasia findings that are found more often with disease duration of over 20 years [35]. Other studies confirmed that DNA aneuploidy is stable, widely spread (hence sampling error is minimal), may precede dysplasia (hence represents an early marker), and is evident 10 years after onset of colitis in young patients [23,25,55,63,68,75,76]. In addition to duration, aneuploidy correlates with extent of disease and is associated with total colitis [23,74].…”
Section: Surveillancementioning
confidence: 91%
“…Aneuploidy represents an early alteration during neoplastic transformation in UC [24,35,68,75]. Holzman et al [35] noted that aneuploidy is present in 8.7% of patients with UC and the frequency increased with increased duration of the disease (>10 years).…”
Section: Surveillancementioning
confidence: 99%
See 3 more Smart Citations